REARING THE BLACK SOLDIER FLY, Hermetia illucens (Linnaeus) (Diptera: Stratiomyidae) IN LOCAL ENVIRONMENTAL CONDITIONS OF BARAMATI (INDIA) - KHYADE, VITTHALRAO B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The efficiency of black soldier fly, Hermetia illucens (Linnaeus, 1758) (Diptera: Stratiomyidae) For the efficient role in decomposition of the organic waste matters deserve appreciations and exert environmental significance. On an average life span of the adult is about twelve to thirteen days. The optimal temperature and relative humidity (RH) for average life span of the adult black soldier fly, Hermetia illucens is 31°C and 80% respectively. As RH goes down (up to sixty percent), the lifespan of the adult get decreased by six days. Larval life was observed to have a lifespan of twenty days (20.0 ± 1.05) days at the temperature 30.15 ± 0.26°C. Larval life was observed to have prolonged span of their lives during season with rain and temperature of about 28°C (from July to November). The adults of the black soldier fly, were reported to lay the eggs even in the absence of decomposing organic matter. Collection of the eggs was carried out from various places such as sponges, cardboards, and in the meshes of the nets used for caging. Near 477 ± 10.69 eggs per batch was the reading for the egg count. The fertilized eggs were observed in the process of development and hatching within 4.5 days on the temperature of 30.15° (± 0.26). Freshly laid eggs were observed to measure 0.901 (± 0.013) millimetre. The duration for emergence of the adult flies from the stage of prepupa was 14.7 (± 1.07) days at the conditions of 30.15° (± 0.26). Total lifespan (from egg to adults) was reported to be 57.8 days at at the conditions of 30.15° (± 0.26). Significant and distinct feature of the black soldier fly, Hermetia illucens (Linnaeus) is to exhibit five morphological instars (or stages). The larval instars of the black soldier fly were found to have a strong positive olfactory reception to decomposed organic wastes than other food sources. The average length (millimetre) of the body of the first, second, third, fourth and fifth instar were 2.35 ± 0.02, 6.45 ± 0.07, 10.26 ± 0.11, 15.92 ± 0.23 and 17.34 ± 0.09. Mean length of the body of the adult fly was 16.92 ± 0.21 millimetre. Mean wingspan of adult male and adult female was 12.25 ± 0.21 millimetre and 13.02 ± 0.23 millimetre respectively.